Transvestism: medical-legal aspects - Kvitko, Luis Alberto (Revista Universidad de Guayaquil, 1983)
Forensic medicine does not have signs that can allow us to affirm that a certain person is an active permissive homosexual. The only thing worth taking into account is the spontaneous and free manifestation that a certain subject makes and prefers to be homosexual. Given this, logically there are limitations. They constitute the fact of not being or being in front of a mentally alienated person. But, in the specific case of transvestites, the mere fact of being in the presence of the person who wears the clothes and acts as if they were of the other sex, simply configures the diagnosis of transvestite.